Care intertwined with anxiety and helplessness: the experiences of ICU nurses from COVID-19 disease’s end of life—a qualitative study - Neda Asadi; Zahra Royani; Sirous Pourkhajoei (BMJ Open)
Objective During the COVID-19 pandemic, the need for end-of-life care has increased. This type of care is different for patients with COVID-19 compared with other patients. This study aims to explain the experiences of intensive care unit (ICU) nurses in providing end-of-life care to patients with COVID-19.Design Qualitative content analysis.Setting The study population consisted of ICU nurses working in hospitals affiliated with the Kerman University of Medical Sciences in southeastern Iran.Participants 14 ICU nurses, including 9 women and 5 men, participated in this study. Their mean age was 33.79±5.07 years, and their mean work experience was 8.64±3.5 years.Primary and secondary objectives The purpose of this qualitative content analysis was to explore the experiences of Iranian intensive care nurses using purposive sampling and semistructured in-depth interviews. Sampling was based on maximum variation (age, gender, professional experience and educational level) to obtain rich information. Guba and Lincoln’s criteria were applied to increase the trustworthiness and rigour of the study, and the data were analysed using Graneheim and Lundman’s method and MAXQDA 2020.Results ICU nurses’ experiences of caring for patients with COVID-19 at the end of life are comprehensive, and four main themes emerged from the responses: fear of death due to COVID-19 infection; physical and psychological consequences of caring for patients dying from COVID-19; confusion in caring for patients with COVID-19 at the end of life and unbelievable deaths.Conclusion The present study looked at the experiences of Iranian nurses providing end-of-life care during the COVID-19 pandemic. The findings suggest that the nurses experienced anxiety, excessive fatigue and guilt during end-of-life care and that the high mortality and unbelievable deaths were traumatic experiences for them.